2005
DOI: 10.1002/elps.200500311
|View full text |Cite
|
Sign up to set email alerts
|

Are the asserted advantages of organic solvents in capillary electrophoresis real? A critical discussion

Abstract: Are the asserted advantages of organic solvents in capillary electrophoresis real? A critical discussionBackground electrolytes (BGEs) prepared in pure organic solvents are common alternatives to aqueous BGEs in capillary electrophoresis. Several general advantages of organic solvents over water have been asserted in the literature, namely (i) organic solvents increase the separation selectivity; (ii) organic solvents increase the separation efficiency; (iii) high separation voltages and/or high BGE ionic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…For small ions, it has already been shown that the inverse of the effective mobility, assuming fully charged species, depends linearly on t/eZ, where Z, t and e are the solvent viscosity, the Debye dielectric relaxation time and the permittivity, respectively [34,35]. However, such general equation does not apply to proteins, since the ACN content will modify not only the pK a of the various acidic and basic sites [36] but will also modify the 3-D structure of the zein proteins [37,38] and thus their electrophoretic mobilities.…”
Section: Effect Of the Acn Contentmentioning
confidence: 95%
“…For small ions, it has already been shown that the inverse of the effective mobility, assuming fully charged species, depends linearly on t/eZ, where Z, t and e are the solvent viscosity, the Debye dielectric relaxation time and the permittivity, respectively [34,35]. However, such general equation does not apply to proteins, since the ACN content will modify not only the pK a of the various acidic and basic sites [36] but will also modify the 3-D structure of the zein proteins [37,38] and thus their electrophoretic mobilities.…”
Section: Effect Of the Acn Contentmentioning
confidence: 95%
“…In NACE, the organic solvent and the electrolyte are the two important parameters for tuning the mobility of EOF (m eof ) and the effective mobility (m ep ), as well as selectivity and resolution [17][18][19]. MeOH, EtOH, and ACN are widely used as the organic media in NACE [20][21][22], and NH 4 Ac [20][21][22] and Tris [23] are commonly used as special buffering group and electrolyte in both CE and NACE.…”
Section: Development Of the Nace Methodsmentioning
confidence: 99%
“…However, MEKC featured some defects such as the longer migration time and complicated BGE composition. Nonaqueous CE (NACE), as an important CE separation mode, is performed in the BGE with an organic solvent medium, it can improve the preservative's solubility, the stability of EOF, the separation resolution, and the reproducibility of the method, due to the presence of the great difference of physicochemical properties between organic and water solvent [17][18][19]. Thus, the aims of the present work are as follows: (i) to develop a practical extraction and cleanup procedure prior to the analysis of BA and SA; (ii) to develop both practical HPLC and NACE methods for the measurement of BA and SA, and (iii) to determine BA and SA in sour snap beans containing oil, using the developed methods.…”
Section: Introductionmentioning
confidence: 99%
“…NACE, as an important CE separation mode, is performed in the BGE with an organic solvent medium. It can improve the separation resolution and the reproducibility of the method, due to the great difference in physicochemical properties between organic and water solvent [42,43]. However, the analysis for nucleotides (especially for AMP isomers) has not been extensively documented by NACE.…”
Section: N-(oo-diisopropyl) Phosphoryl Amino Acid (Dipp-aamentioning
confidence: 99%
“…Among these methods, HPLC is most widely used, due to its high separation performance, for the determination of nucleotides in many different samples [22][23][24][25][26][27][28][29][30][31]. As an alterative method, CE has been widely utilized in the nucleotide analysis in recent years [32][33][34][35][36][37][38][39][40][41][42] due to CE having many advantages over the traditional HPLC. Therefore, in this paper, we try to develop a practical CE method for the simultaneous measurement of three AMP isomers in the biomimicking prebiotic synthesis samples.…”
Section: N-(oo-diisopropyl) Phosphoryl Amino Acid (Dipp-aamentioning
confidence: 99%